The Impact of Global Equity Offerings - Chaplinsky, Susan; Ramchand, Latha (Journal of Finance, 2000)
This article examines the impact of U.S. firms issuing equity in multiple markets. We compare the stock price reactions to announcements of global equity offers to a control group of issues offered exclusively in the domestic U.S. market. All else equal, the adverse price reaction that typically accompanies equity issuance is reduced by 0.8 percent when some shares are sold abroad. The overall evidence suggests global offers are effective in expanding demand and reducing the price pressure effects associated with share issuance. The beneits of global offers appear to be associated with an increase in the number of foreign shareholders.